Bichromophoric rhodamine-rhenium(I) and -iridium(III) sensory system: Synthesis, characterizations, photophysical and selective metal ions binding studies. (28th January 2015) - Wong, Keith Man-Chung; Wang, Chunyan; Lam, Ho-Chuen; Zhu, Nianyong
Graphical abstract: A new class of rhenium(I) tricarbonyl diimine complexes tethered with rhodamine derivative, have been synthesized, and their photophysical and selective ion-binding properties investigated, with the comparison of the cyclometalated iridium(III) system. Abstract: A new class of rhenium(I) tricarbonyl diimine complexes containing rhodamine derivative as a sensory moiety, have been synthesized and characterized. Their photophysical and selective ion-binding properties have also been investigated, with the comparison of the previously reported cyclometalated iridium(III) system. One of the complex was found to exhibit selective binding toward Hg(II) ion with electronic absorption and emission spectral changes. On the other hand, the iridium(III) complexes were found to give similar electronic absorption response but different emission spectral changes upon addition of Hg(II) ion. Interestingly, efficient intramolecular energy transfer from rhodamine 6G to the cyclometalated iridium(III) moiety was suggested in one of the complexes, which could be modulated by selective ion-binding process upon ring-opening of rhodamine 6G. This report shows that the modification of rhodamine derivatives and the choice of transition metal ion could be important to influence the selective binding properties for development of colorimetric and/or luminescent probe.